Adsorption of bentazon on two kinds of granular activated carbons: equilibrium, kinetic and thermodynamic studies. Issue 59 (19th December 2016) - Wei, Xingya; Gao, Naiyun; Li, Changjun; Deng, Jing; Zhu, Yanping; Wang, Qiongfang
Abstract: The adsorption of bentazon on two types of granular activated carbons (GACs), VRU F36X16 (VRU) and WS-480 (WS) from aqueous solution was evaluated by kinetics, isotherms, and thermodynamic models in this study. The impacts of initial bentazon concentration, temperature, and initial solution pH were also investigated. The equilibrium adsorption capacity ( q e ) of each GAC was appreciable under the experimental condition, especially VRU. For either GAC, the adsorption process fitted pseudo-second-order equation best and statistics matched two-step intra-particle diffusion model well. Dubinin–Radushkevich model was the most suitable one for bentazon adsorption on VRU, while Redlich and Peterson model best described bentazon adsorption on WS. Both for VRU and WS, the adsorption process was exothermic and belonged to physisorption. The q e of VRU and WS increased as initial bentazon concentration increased, though the removal rate of bentazon decreased. 25°C was the optimal condition for bentazon adsorption on either GAC, while the q e of both GACs dropped as the temperature increased. Although the increase in pH could hinder bentazon adsorption on GACs significantly, there was a slight change in the adsorption capacities of VRU and WS when initial solution pH was in the range 5–9.